OC-139 Time trends in rates of first surgical resection and thiopurine use in crohn's disease: retrospective cohort study. (28th May 2012) - Chatu, S; Saxena, S; Subramanian, V; Curcin, V; Yadegarfar, G; Majeed, A; Pollok, R C
Abstract : Introduction: The efficacy of thiopurines in treating Crohn's disease is well established but their role in altering the long term natural history of Crohn's disease remains controversial. Using a national population based cohort we aimed to determine temporal trends in surgery and use of thiopurines. Methods: We undertook a retrospective study of electronic medical records from primary care. We identified newly diagnosed patients with Crohn's disease between 1989 and 2005 in the General Practise Research database (GPRD) which contains prescription and clinical data for over 13 million people in the UK and has been validated for research. Incident cases were eligible if registered for more than 12 months before their diagnosis. Patients were allocated to three cohorts according to year of diagnosis: group A (1989–1993), group B (1994–1999) and group C (2000–2005). We calculated rates of first surgical resection and thiopurine prescribing (azathiopurine and 6-mercaptopurine) within 5 years of diagnosis to examine temporal trends. Results: 5654 patients met our inclusion criteria. The mean age was 37 years and 57% were female. During the study period from 1989 to 2010 rates of intestinal surgery decreased while prescription of thiopurines increased. Rates of first surgery were 17, 11, and 6/1000/year (χ 2 p<0.05) and thiopurine prescriptions were 27, 33 and 45/1000/year (χ 2 p<0.05) in groups A, B and C respectively. Furthermore rates of thiopurine prescription within the first year of diagnosis were 11, 15, and 26/1000/year (χ 2 p<0.05) in groups A, B and C respectively. Conclusion: Rates of first surgical resection have markedly decreased with concomitant earlier and increased use of thiopurines over the same time frame. Further work is proposed to explain these trends. Competing interests: None declared.